Solubility improvement and Dissolution enhancement of Simvastatin using Fluidized Hot-Melt Granulation Technique (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
A fluidized hot melt granulation (FHMG) technique was used to enhance the solubility and dissolution of simvastatin. Employing meltable hydrophilic binders and then converting the melt dispersion into flowable and compressible dispersion granules to yield a rapidly dissolving tablet formulation. Granules prepared by using hydrophilic polymer polyethylene glycol 4000 or 6000, Gelucire 50/13 or 44/14, and Poloxamer 188 or 407, spray-dried lactose as a fluidized substrate. The binder used for spray granulation in this technique was a mixture of molten Gelucire 50/13 and simvastatin. Phase Solubility studies showed an increase in solubility ratio of 1:4 for Simvastatin: Gelucire 50/13. The prepared granules were characterized using FTIR, and DSC spectra exhibited drug excipients compatibility. XRD data exhibited a partial loss of crystallinity as indicated by significantly less intensity of simvastatin peak in a sample than pure simvastatin. Tablets with the faster dissolution of simvastatin (98.99% of the drug release with 30 minutes). This was achieved with lactose/MCC as filler. A significant enhancement in-vitro dissolution profile of the melted granules was observed compared to the pure drug and marketed product. Therefore, the results confirmed the high potential of the FHMG technique to produce granules with enhanced drug solubility and release rate.